2013
DOI: 10.1155/2013/139049
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Metabolic Syndrome One Year after Delivery in Finnish Women at Increased Risk for Gestational Diabetes Mellitus during Pregnancy

Abstract: Background. Women with a history of gestational diabetes mellitus (GDM) are at increased risk for metabolic syndrome (MeS) after delivery. We studied the prevalence of MeS at one year postpartum among Finnish women who in early pregnancy were at increased risk of developing GDM. Methods. This follow-up study is a part of a GDM prevention trial. At one year postpartum, 150 women (mean age 33.1 years, BMI 27.2 kg/m2) were evaluated for MeS. Results. The prevalence of MeS was 18% according tothe International Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 31 publications
0
23
1
Order By: Relevance
“…After full‐text review, 71 studies still met inclusion and exclusion criteria. Of these, a total of 18 studies reported on the same study populations; we selected one to report on going forward: four used Project Viva (34–37; 35 reported); three used Kaiser Permanente Northern California (26, 38, 39; 38 and 39 reported); two used the Generation R study in the Netherlands (40,41; 40 reported); two used the Danish National Birth cohort (42,43; 43 reported); two used the Asthma Coalition on Community, Environment and Social Stress cohort (44,45; 44 reported); two used the Mater‐University of Queensland Study of Pregnancy (46,47; 47 reported); two used the National Collaborative Perinatal Project (NCPP) (48,49; both reported) and two studies used the NELLI cohort in Finland . For the NCPP population, we report findings for both studies because they report results at different times during pregnancy.…”
Section: Resultsmentioning
confidence: 99%
“…After full‐text review, 71 studies still met inclusion and exclusion criteria. Of these, a total of 18 studies reported on the same study populations; we selected one to report on going forward: four used Project Viva (34–37; 35 reported); three used Kaiser Permanente Northern California (26, 38, 39; 38 and 39 reported); two used the Generation R study in the Netherlands (40,41; 40 reported); two used the Danish National Birth cohort (42,43; 43 reported); two used the Asthma Coalition on Community, Environment and Social Stress cohort (44,45; 44 reported); two used the Mater‐University of Queensland Study of Pregnancy (46,47; 47 reported); two used the National Collaborative Perinatal Project (NCPP) (48,49; both reported) and two studies used the NELLI cohort in Finland . For the NCPP population, we report findings for both studies because they report results at different times during pregnancy.…”
Section: Resultsmentioning
confidence: 99%
“…21 In our earlier report of the same original trial, the MeS prevalence among women with early GDM was already elevated (31%) at 1-year postpartum compared with the intervention group (11%). 24 Seven years postpartum, the MeS prevalence among women with early GDM had increased to 50%. Further, women with early GDM had increased odds for MeS compared with other three groups (intervention, usual care and healthy controls).…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30][31] One year after delivery, the prevalence of MeS among women with GDM risk factors was 16-18% depending on the criteria; with no differences between the intervention and usual care group. 24 Our aim is to study MeS and its components 7 years postpartum among Finnish women who in early pregnancy were at increased risk of developing GDM (intervention or usual care), among women with early pregnancy GDM diagnosis and among women without GDM risk factors during pregnancy (healthy control). We also studied risk factors associated with the development of MeS 7 years postpartum.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have indicated that the prevalence of metabolic syndrome among Finnish women with a history of gestational diabetes mellitus at 1 year post partum was 18% [25], and the prevalence of metabolic syndrome among USA and Denmark women with a history of gestational diabetes mellitus at 10 years post partum was 30–40% [26,27]. As the prevalence of metabolic syndrome increases with a post-partum duration, an early post-partum lifestyle intervention of women with a history of gestational diabetes mellitus [13] is important for prevention of cardiometabolic implications, especially for prevention of high prevalence of elevated waist circumference, reduced HDL-C and elevated glucose.…”
Section: Discussionmentioning
confidence: 99%